POLYGALA PANICULATA L. SEBAGAI ALTERNATIF TANAMAN OBAT DI TAMAN OBAT KELUARGA - SUTOMO SUTOMO (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2007)
ABSTRACT Polygala paniculata L. grows naturally in grasslands, open woodland or even in our own backyard. But most people only see P. paniculata as a weed or wild grass instead of a medicinal plants. This paper is going to discuss about a profile of P. paniculata in order to promote this species as a medicinal plant.